ANALYSIS OF TERRESTRIAL HYPERCONCENTRATED FLOWS AND THEIR DEPOSITS - Benvenuti M.; Martini I.P. (My University, 2002)
The term hyperconcentrated flow refers to intermediate states between debris flows and fluid flows, where fluid turbulence remains an important dispersal mechanism of clastic particles. Whereas the end-member flows are fairly well understood, unanimous agreement has not been reached on the subdivision and boundary definition of hyperconcentrated flows, both in meaningful rheological terms and, more so, in terms of the characteristics of their deposits. This paper briefly reviews the main characteristics of hyperconcentrated flows resulting from either suspended-load hyperconcentration or bedload hyperconcentration (traction carpet), and focuses on the analysis of three deposits possibly associated with these flows. The first two deposits formed in ancient, temperate alluvial fans of Pliocene–Pleistocene post-collision basins of the Northern Apennines, Italy, and the third in Upper Pleistocene glacial outwash of Ontario, Canada. The main finding is that geomorphological setting, climate and substrate geology are the prime control for hyperconcentrated flows in terms of frequency, magnitude and rheological properties of the flow. Recognition of hyperconcentrated-flow deposits through facies analysis leads to a better understanding of the developmental dynamics of alluvial sediment succession, and provides powerful information for risk assessment of localities possibly affected by hydrogeological hazards.